Benefits (and Losses) From Rent Control in the Philippines: An Empirical Study of Metro Manila - Marife M. Ballesteros (Philippine Institute for Development Studies (PIDS), 2001)
This study examines benefits of rent control law in Metro Manila. The results show that rent control benefits are conditional to occupying a rent-controlled unit and on tenure. The benefits of rent control are found positive. Many poor and low-income households are benefited but the distributional effects are minimal since nonpoor families have equal access to rent-controlled units. Evidence of losses or income transfers from landlords to tenants is not substantiated. The most probable income transfers are those from short-stayers to long-stayers. Rent control is a poor mechanism for income transfer. However, the rental housing market tend to be monopolistic and rent control maybe necessary to prevent economic eviction and abuses on payment of key monies. In this case, government has to provide better monitoring mechanism and ensure enforcement of lease contracts.
Keywords: 330; rent control; rental housing market; Mietenpolitik; Wirkungsanalyse; Kritik; Philippinen; Manila